2018
DOI: 10.1186/s12966-018-0682-4
|View full text |Cite
|
Sign up to set email alerts
|

Results of a feasibility cluster randomised controlled trial of a peer-led school-based intervention to increase the physical activity of adolescent girls (PLAN-A)

Abstract: BackgroundMost adolescent girls in the UK do not meet government physical activity recommendations and effective interventions are needed. This study reports the results of a feasibility trial of PLAN-A, a novel school-based peer-led physical activity intervention for adolescent girls.MethodsA two-arm cluster randomised controlled feasibility study was conducted in six English secondary schools (4 intervention & 2 control). Year 8 (age 12-13) girls were eligible and randomisation was at school-level. The inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(147 citation statements)
references
References 41 publications
5
108
1
Order By: Relevance
“…Self-reported responses to HRQoL measures by participants in the intervention arm and the control arm were similar at baseline and follow-up. This finding is consistent with previous studies 57,62 in which HRQoL measures were found to be unresponsive among school children with 'healthy' profiles and supports the case for considering alternative HRQoL measures that are appropriate for use with this population.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Self-reported responses to HRQoL measures by participants in the intervention arm and the control arm were similar at baseline and follow-up. This finding is consistent with previous studies 57,62 in which HRQoL measures were found to be unresponsive among school children with 'healthy' profiles and supports the case for considering alternative HRQoL measures that are appropriate for use with this population.…”
Section: Resultssupporting
confidence: 91%
“…Unfortunately, the funding landscape makes securing funds specifically to create and test these measures with children very difficultyet without them our ability to measure the effects of our interventions on potential mediators is limited. 57,61,62 The majority of extracurricular physical activity provision provided by schools in this study was funded by the school or parents and this finding is comparable with the results of an audit of after-school club provision for children in Years 5 and 6 from primary schools in England. 19 Notably, estimated Action 3:30 costs were found to compare favourably with the costs associated with existing extra-curricular physical activity delivered in study schools.…”
Section: Impact Of the Action 3:30 Programme On Motivationsupporting
confidence: 80%
See 1 more Smart Citation
“…We have recently reported the protocol [13] and findings [14] of a feasibility study of PLAN-A, a Peer-Led physical Activity iNtervention for Adolescent girls. The PLAN-A intervention is based on a previously effective stop-smoking intervention, A Stop Smoking in Schools Trial (ASSIST) [15], which used informal peer-diffusion to spread positive messages and develop new norms for health behaviour (for ASSIST, not smoking; for PLAN-A, being physically active).…”
Section: Introductionmentioning
confidence: 99%
“…We conducted a feasibility cluster randomised controlled trial of the PLAN-A intervention in six secondary schools (four intervention, two control) involving 427 Year 8 girls. Measures of intervention feasibility and objective assessments of girls' MVPA at baseline, 10 weeks and 5 months follow up were collected [14]. We found that school, participant, trainer and peer-supporter recruitment and retention were feasible, that data required to evaluate the intervention could be collected and that 94% of peer-supporters attended all of the training.…”
Section: Introductionmentioning
confidence: 99%